Cystatin C-Based eGFR Predicts Post-Treatment Kidney Prognosis in Patients with Severe Obstructive Nephropathy - Kunihiro Nakai; Hiroyoshi Segawa; Masatomo Yashiro; Kengo Yoshii; Tetsuro Kusaba; Satoaki Matoba; Keiichi Tamagaki; Tsuguru Hatta; Hiroshi Kado (MDPI AG, 2022)
A discrepancy between serum concentrations of cystatin C (CysC) and creatinine (sCr) has been reported in patients with acute obstructive nephropathy. However, the usefulness of CysC for predicting the recovery of kidney function in patients with severe obstructive nephropathy remains unclear. We examined the predictability of the estimated glomerular filtration rate calculated with CysC or sCr (eGFRcys or eGFRcreat) for the post-treatment recovery of kidney function. We retrospectively collected patients with severe obstructive nephropathy (eGFRcreat < 30 mL/min/1.73 m2) whose baseline sCr and CysC were measured between 48 h before and 24 h after the release of urinary tract obstruction (UTO). The primary outcome was recovery from severe eGFRcreat depression (i.e., eGFRcreat ≥ 30 mL/min/1.73 m2) 7 days after the release of UTO. We calculated the area under the curve (AUC) of the receiver operating characteristic (ROC) curve for the relationship between eGFRcys or eGFRcreat and recovery. Thirty-four patients (20 males) with a median age of 76 years were eligible. We identified 20 recovery cases. The AUCs of the ROC curves (95% confidence interval) for eGFRcys and eGFRcreat were 0.81 (0.66-0.96) and 0.53 (0.32-0.73), respectively. These results imply cystatin C-based eGFR may help predict kidney prognosis in patients with severe obstructive nephropathy.